2006
DOI: 10.1007/s11575-006-0044-3
|View full text |Cite
|
Sign up to set email alerts
|

Turbulence, discovery and foreign market entry: A longitudinal study of an entry into the Russian market

Abstract: ■ Firms entering transition markets are typically ignorant about those markets, and the markets, owing to the transition from a planned to a market economy, are typically turbulent. Consequently the entry process involves discoveries that could not have been predicted in advance. This position is supported by a longitudinal study in real-time of a Swedish firm's entry into the Russian market between 1987 and 1993.■ The paper distinguishes between three types of activity that form part of the entry process, nam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
18
0
1

Year Published

2006
2006
2020
2020

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 33 publications
(20 citation statements)
references
References 32 publications
1
18
0
1
Order By: Relevance
“…It is advocated that the stage model should be extended to incorporate the importance of knowledge about host market policy environments as well as the role of home country contexts in choosing the optimal investment timing (see Delios & Henisz, 2003). In their longitudinal study, Johanson and Johanson (2006) found that firms also made new knowledge discoveries throughout the FME process, particularly in transition economies with high degrees of uncertainty.…”
Section: Stage-evolutionary Model Of Internationalisation: Is It Stilmentioning
confidence: 99%
“…It is advocated that the stage model should be extended to incorporate the importance of knowledge about host market policy environments as well as the role of home country contexts in choosing the optimal investment timing (see Delios & Henisz, 2003). In their longitudinal study, Johanson and Johanson (2006) found that firms also made new knowledge discoveries throughout the FME process, particularly in transition economies with high degrees of uncertainty.…”
Section: Stage-evolutionary Model Of Internationalisation: Is It Stilmentioning
confidence: 99%
“…Russian firms tend to prefer to terminate relationships rather than changing activities within the relationships (Hallén & Johanson, 2004b, Johanson, 2004a. This development is strengthened by the fact that during the transition knowledge about how to do business becomes obsolete and no longer valid, and firms have to find new ways of doing business, which often also tends to mean finding new customers and suppliers (Johanson, 2004b;Johanson and Johanson, 2006).…”
Section: Timementioning
confidence: 99%
“…The question of what happens when the situation suddenly deteriorates, and 'contingent uncertainty' increases, needs further analysis and empirical testing. There is some evidence that unstable (and uncertain) environments require a tenuous compromise between knowledge and commitment decisions (Johanson & Johanson, 2006).…”
Section: Internationalization Process and Uppsala Modelmentioning
confidence: 99%